2019
DOI: 10.1177/0361198119844244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Visual and Auditory Alerts on Older Drivers’ Glances toward Latent Hazards while Turning Left at Intersections

Abstract: Older drivers are known to make significantly fewer glances toward hazards that are hidden from view (latent hazards) than middle-aged drivers. This is especially true when the driver is making a left turn at an intersection at that critical point in the turn immediately after the driver enters the intersection. This has led to the development of training programs that can increase the frequency of these glances toward latent hazards at intersections. However, training programs can require time and money that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In other words, if the driver reaches the triggering point located at 55.6 m from the pedestrian crossing with a higher or a lower speed of 50 km/h, the values of the time to collision will be lower or higher, re-spectively, than 4 s. It should be noted that, taking into account the variability of the approaching speeds at the pedestrian crossing, the actual values of the time to collision in the moment in which the warning is triggered recorded during the simulated drives, are expected in the interval between 2.8 and 6.5 s (2.8 s for speed equal to 70 km/h and triggering point 55.6 m from the pedestrian crossing; 6.5 s for speed equal to 30 km/h and triggering point 55.6 m from the pedestrian crossing). Such values are fully consistent with those reported in literature (Scott, Gray 2008;Yan et al 2015b;Hajiseyedjavadi et al 2018;Bakhtiari et al 2019). In other terms, the design of the experiment implies the simulation of ADAS in which the time to collision values are fully consistent with those suggested in literature.…”
Section: Driving Simulator and Road Scenariossupporting
confidence: 89%
“…In other words, if the driver reaches the triggering point located at 55.6 m from the pedestrian crossing with a higher or a lower speed of 50 km/h, the values of the time to collision will be lower or higher, re-spectively, than 4 s. It should be noted that, taking into account the variability of the approaching speeds at the pedestrian crossing, the actual values of the time to collision in the moment in which the warning is triggered recorded during the simulated drives, are expected in the interval between 2.8 and 6.5 s (2.8 s for speed equal to 70 km/h and triggering point 55.6 m from the pedestrian crossing; 6.5 s for speed equal to 30 km/h and triggering point 55.6 m from the pedestrian crossing). Such values are fully consistent with those reported in literature (Scott, Gray 2008;Yan et al 2015b;Hajiseyedjavadi et al 2018;Bakhtiari et al 2019). In other terms, the design of the experiment implies the simulation of ADAS in which the time to collision values are fully consistent with those suggested in literature.…”
Section: Driving Simulator and Road Scenariossupporting
confidence: 89%
“…Another recent study utilised a driving simulator to investigate the effectiveness of visual and auditory warning alerts on older drivers' ability to anticipate threats while turning left at intersections (Bakhtiari et al, 2019). The results showed that across 8 scenarios, the in-vehicle warning system helped drivers anticipate (S. stands for Success (Effectiveness of the Countermeasure); Lit.…”
Section: Driver Warning Systemsmentioning
confidence: 99%
“…Based on accident databases, causes related to vehicle, environment, and road factors affecting the occurrence of accidents have been investigated by researchers through various studies [14]- [23]. Previously, various studies have focused on the causes of accidents, especially human factors as a considerable factor of accidents [4] [5] [6] [7] [17] [20] [21] [22]. For instance, Young et al (2018) reported the possible effects of texting while driving as a human error factor [23].…”
Section: Problem Importance and Research Goalmentioning
confidence: 99%